Non-Newtonian Turbulent Tsunami Mudflow Impact on a Vertical Structure: An Experimental Approach - PHILIP, AARON KEITH (2019)
Tsunami in the form of bores or surges at the coastal region often transport massive amount of sediments in the water body. The presence of sediments in water even at 5% volumetric concentration is known to induce non-Newtonian behavior specifically conforming to the Herschel-Bulkley model. In response to the limited design guidelines for the design of tsunami resistant structures, the US Federal Emergency Management Agency (FEMA) introduces the FEMA P-646 guideline